2021
DOI: 10.1097/pec.0000000000002376
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Myopericarditis Presenting to the Emergency Department as Chest Pain

Abstract: Objectives: Myopericarditis is a newly described entity that is primarily a pericardial syndrome with elevated cardiac enzymes that has been seen with increasing frequency in our pediatric intensive care unit. For this reason, we performed a retrospective cohort analysis with a goal of establishing differences between myopericarditis and myocarditis that could lead to proper diagnosis on emergency department presentation.Methods: A database query was performed and identified patients over a 9-year period, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“… 3 , 5 In the literature, there is a prominent male predominance. 5 , 8 Also in our study, 74% of the patients was male.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“… 3 , 5 In the literature, there is a prominent male predominance. 5 , 8 Also in our study, 74% of the patients was male.…”
Section: Discussionsupporting
confidence: 63%
“…Depending on ECG findings, Başar et al 5 reported ventricular premature beats in 5.1%, and supraventricular tachycardia in 2.6% of 39 children. Babbitt et al 8 did not make a comment about the frequency of arrhythmias between children with myopericarditis and true myocarditis. In none of the above studies, 24-hour Holter monitorization had been performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations